Acute Posttransfusion Lung Injury: State-of-the-Art - A. V. Vlasenko; D. P. Pavlov; A. V. Cheparnov; D. A., Ostapchenko; A. K. Doloksaribu; D. A. Shestakov; V. N. Yakovlev; A. V. Shabunin (Общая реаниматология, 2008)
Based on the analysis of the references given in the Russian and foreign periodicals, the present paper states the current notions of the etiology, epidemiology, and pathogenesis of and the methods for the diagnosis, prevention, and treatment of acute lung injury developing with the use of blood preparations. It shows the difficulties arising in the diagnosis of this complication and presents the algorithms of differential diagnosis and treatment of acute posttransfusion lung injury. The authors describe their own observation of a case of evolving acute posttransfusion lung injury, the used methods of diagnosis, and the results of treatment in detail.